Incivility among library staff in private universities in southwest Nigeria: a five-year evaluation - Akintola, Bosede Olutoyin; Adeeko, Christy Olabisi; Adebamiro, Ayokari Adenike; Adio, Samuel K. (Communicate: Journal of Library and Information Science, 2025)
This study assessed incivility among library staff in private universities in Southwest Nigeria in the previous five years. The study was conducted via the survey method. Total enumeration method was employed to elicit data from all the library staff in six private universities across four states in southwest Nigeria. An online structured questionnaire adapted from Cortina (2001) was used for data collection, it was circulated via the Google Form Platform and some hard copies- 69 copies were found usable. Data collected were analysed using descriptive statistics, tables of frequencies and percentages. Findings revealed that all the 17 listed uncivil behaviors had been experienced by respondents at different times and frequencies. Such as, being shouted at, ignored, disrespected, addressed in unprofessional terms, taking credit for another’s work. The total cumulative responses /frequency of occurrence across all the 17 listed uncivil behaviors, showed that a cumulative total of 401 (34.17%) respondents experienced uncivil behaviors once or twice a year, 203 (17.29%) every day, 108 (9.19%) once or twice a month, 58 (4.92%) about once a week and 50 (4.16%) several times a week while 354 (30.17%) did not experience uncivil behaviors. The most common strategy to combat incivility are, “supervisors are to effectively convey vision to subordinates for clarity of duties” 67(97.1%). Others rated equally with 65(94.2%) are: “staff should respect one another; do self-reflection/self-examination for positive change in behavior; maintain good interpersonal communication and bosses should be role models”. Due punishment for uncivil behaviors ranked third, 64 (92.8%) while the least ranked was “it is better to retaliate and be uncivil to the uncivil staff, 19 (27.5%)”. The study recommended policy formation, implementation, trainings and punishment for incivility, and libraries should focus more on this phenomenon.